Di-mu-bromo-bis[bromo(eta(6)-para-cymene)-ruthenium(II)] benzene solvate and di-mu-iodo-bis[(eta(6)-para-cymene)iodoruthenium(II)] toluene solvate - Neels, Antonia; Stoeckli-Evans, Helen; Plasseraud, Laurent; Fidalgo, Eva Garcia; Süss-Fink, Georg (My University, 1999)
The homologous title molecules, [Ru2Br4(C10H14)(2)]. C6H6, (1), and [Ru2I4(C10H14)(2)]. C7H8, (2), consist of arene-ruthenium moieties [Ru-to-ring distances of 1.655 (2) Angstrom in (1) and 1.673(3) Angstrom in (2)] with a terminal halogen ligand and [Ru-Br 2.548 (1) Angstrom in (1) and Ru-I 2.726(1) Angstrom in (2)], held together by two symmetrical halogen bridges [Ru-Br 2.575(1) Angstrom in (1) and Ru-I 2.736(1) Angstrom in (2)]. The arene rings are planar and parallel to each other, and the terminal halogen ligands are coordinated to rurthenium trans with respect to each other. Both molecules possess C-i symmetry.
Keywords: RUTHENIUM; COMPLEXES